أثر إستراتيجية فن الاستذكار في تحسين تعليم المفردات لدى طلاب الصف الخامس بمدرسة الهداية الابتدائية الإسلامية ديبوك - Ambarsari, Citra Shofa; Siti Uriana Rahmawati; Achmad Fudhaili (INTIFA: Journal of Education and Language, 2025)
The researcher chose this topic due to problems in Arabic vocabulary learning, such as students’ difficulty in remembering new words and teachers’ inaccuracy in selecting appropriate strategies and modern media. Therefore, it is necessary to apply an effective strategy to improve vocabulary learning. This study aims to determine the effect of the mnemonic strategy in improving vocabulary related to body parts, professions, and animal characteristics among fifth-grade students of MI Al-Hidayah Depok. The researcher employed a mixed-method approach with an Explanatory Sequential Design, combining quantitative and qualitative methods. The quantitative stage used a quasi-experimental one-group pretest-posttest design, analyzed through normality, N-Gain, and correlation tests. The results showed that the mnemonic strategy had a positive effect on vocabulary learning, as the average score increased from 61.76 (pretest) to 81.28 (posttest), with an N-Gain of 0.4861 (medium effect). The significance value (Sig. 2-tailed) was 0.011 < 0.05, indicating rejection of the null hypothesis and acceptance of the alternative. The study concludes that the mnemonic strategy effectively enhances students’ vocabulary mastery. These findings highlight the importance of implementing creative and memory-based strategies in Arabic language teaching to foster better learning outcomes. Keywords : Mnemonics, Arabic Vocabulary, Vocabulary Learning